Mcp7, a meiosis-specific coiled-coil protein of fission yeast, associates with Meu13 and is required for meiotic recombination - Saito, Takamune T. (Oxford University Press, 2004)
We previously showed that Meu13 of Schizosaccharomyces pombe functions in homologous pairing and recombination at meiosis I. Here we show that a meiosis-specific gene encodes a coiled-coil protein that complexes with Meu13 during meiosis in vivo. This gene denoted as mcp7(+) (after meiotic coiled-coil protein) is an ortholog of Mnd1 of Saccharomyces cerevisiae. Mcp7 proteins are detected on meiotic chromatin. The phenotypes of mcp7Δ cells are similar to those of meu13Δ cells as they show reduced recombination rates and spore viability and produce spores with abnormal morphology. However, a delay in initiation of meiosis I chromosome segregation of mcp7Δ cells is not so conspicuous as meu13Δ cells, and no meiotic delay is observed in mcp7Δmeu13Δ cells. Mcp7 and Meu13 proteins depend on each other differently; Mcp7 becomes more stable in meu13Δ cells, whereas Meu13 becomes less stable in mcp7Δ cells. Genetic analysis shows that Mcp7 acts in the downstream of Dmc1, homologs of Escherichia coli RecA protein, for both recombination and subsequent sporulation. Taken together, we conclude that Mcp7 associates with Meu13 and together they play a key role in meiotic recombination.